Diagnosis and monitoring of chromosome aberrations in hematological malignancies by fluorescence in situ hybridization - Döhner, Hartmut; Stilgenbauer, Stephan; Döhner, Konstanze; Schröder, Martin; Bentz, Martin; Lichter, Peter (Stem cells, 1995)
Besides its application in biological research, fluorescence in situ hybridization (FISH) is increasingly used for the cytogenetic analysis of human malignancies. Compared to conventional cytogenetic analysis, FISH allows delineation of specific numerical and structural chromosome aberrations in interphase cells (interphase cytogenetics). We have developed sets of genomic DNA probes for the identification of chromosome aberrations associated with chronic lymphocytic leukemia (CLL), chronic myeloid leukemias (CML), and acute myeloid leukemia (AML). In CLL, interphase cytogenetics will greatly contribute to the evaluation of the true incidence of specific chromosome aberrations and will provide the basis for more accurate correlations with the clinical outcome. The Philadelphia chromosome can be detected by FISH with high specificity and sensitivity in both CML and acute lymphoblastic leukemia. In CML, it can be used to better assess the cytogenetic remission status following therapy with interferon-alpha. Finally, in AML interphase cytogenetics provides a rapid and reliable technique for the identification of chromosome aberrations which are one of the most important prognostic factors in this disease. With the design of complex DNA probe sets and the development of digital microscopy and automated image analysis, it will be possible to use such disease-specific probe sets for monitoring residual disease following chemotherapy.